WEBSITE INTERFACE MONITORING CLIENT ACTIVITIES USING MIKROTIK ON UBUNTU SERVER 18.04 LTS - Akbar, Lalu A. Syamsul Irfan; Putra, Rayasa Puringgar Prasadha; Ariessaputra, Suthami (Jurusan Teknik Elektro Fakultas Teknik Universitas Mataram, 2023)
Internet network is beneficial to be able to support the needs of the learning process. However, a large number of internet users, for example, who access university data, can cause weaknesses in a system, making it very vulnerable to data theft, damage, and leakage of confidential documents. The obstacle faced is that the internet is getting slower due to many users using the internet network and not knowing the amount of bandwidth usage. A system is needed to determine the bandwidth usage for each client. This system To simplify the process of monitoring the internet network. It can view client browsing history and block website domains so that internet users in the world of education have positive characteristics and the internet is not slow. In this system, the admin will monitor the use of internet clients connected to the campus environment through the user name and password obtained for each student. The results of this research are the creation of an internet monitoring system for a proxy to monitor the maximum amount of bandwidth usage for each client, view the client's browsing history, and block website domains and client IPs. The admin can observe the internet network and monitor client activity that uses the internet network in the campus environment using the monitoring application.